A descriptive study of ten-year longitudinal changes in weight and waist circumference in the multi-ethnic rural Northern Norway. The SAMINOR Study, 2003-2014 - Jacobsen, Bjarne K.; Melhus, Marita; Kvaløy, Kirsti; Siri, Susanna Ragnhild; Michalsen, Vilde Lehne; Broderstad, Ann Ragnhild (PLOS ONE, 2020)
The obesity epidemic is dynamic with varying secular trends and differences between countries and ethnic groups. The objective of this study was to describe the age- and sex-specific longitudinal changes in weight and waist circumference in a rural Norwegian population with a high proportion of the indigenous Sami population. Based on two population-based surveys, SAMINOR 1 (2003–2004) and SAMINOR 2 (2012–2014), we present longitudinal changes in weight and waist circumference according to age at baseline in the SAMINOR 1 Survey and sex during the 10-year period. The analyses included 1538 men and 1958 women aged 36 to 69 at baseline (birth year 1934 to 1967). Forty-one percent of the population were Sami. Both weight and waist circumference were measured. The mean weight increased 0.8 kg (95% confidence interval: 0.5, 1.1) in men and 0.3 kg (95% confidence interval: 0, 0.5) in women. In both men and women, younger individuals gained significantly more weight during the 10-year follow-up than older participants (p < 0.001). The mean weight showed a statistically significant increase in men aged 36–54 and women aged 36–49 at baseline and was statistically significantly reduced in men and women aged 60–69. The mean waist circumference increased by 6.3 cm (95% confidence interval: 6.0, 6.6) in men and 8.4 cm (95% confidence interval 8.1, 8.8) in women. The mean waist circumference increased statistically significantly from SAMINOR 1 to SAMINOR 2 in all age groups, and there was an inverse relationship between age at baseline and change in waist circumference (p < 0.001). Waist circumference increased more than can be explained by changes in weight and age during the 10-year period. The inverse relationships between age at baseline in SAMINOR 1 and the 10-year change in weight and waist circumference were found in both Sami and non-Sami participants. The findings underline the need for prevention of obesity, particularly in younger people, as it is difficult to achieve permanent weight loss.